Invest in Gold Now at PC.Gunungsitoli : Safe Investment, Comfortable Future - Maria Magdalena Bate’e; Calvin Andika Telaumbanua; Asilika Waruwu; Franky Kristian Mendrofa; Ellen Carolina Putri Daeli; Noriwati Lase; Irene Zega; Putri Amirah Hafidz Harefa; Azeti Harefa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Gold investment is increasingly popular among the public, especially in CP. Gunungsitoli, as one of the gold trading centers. This study aims to explore the gold investment process, benefits, challenges faced by investors, and evaluate the effectiveness of gold investment services in the area. Through literature studies, qualitative and quantitative data collection, and observations, this study found that investors in CP. Gunungsitoli considers gold as a safe and stable asset, especially in the face of economic uncertainty. Although there are risks, such as price fluctuations and potential fraud, people are increasingly aware of the importance of diversifying their portfolios by including gold. The results of the study show that ease of access and quality of information greatly influence gold investment decisions. Local gold shops and digital platforms offer various conveniences, but challenges remain in the form of cyber risks and additional costs. This study is relevant in the local context, providing insight into the dynamics of the gold market and the importance of education for investors. With the right recommendations, it is hoped that people can undergo gold investment with more confidence, making it a safe and comfortable choice for the future.